(untitled) (Applied Biological Research, 2019)
The present study was aimed to assess the effects of various adiposity indicators i.e. body mass index (BMI), waist circumference (WC), waist-to hip ratio (WHR), waist-to-height ratio (WHtR) on the causation of blood pressure among Bhil tribal population of India. In this population based cross sectional study, a total of 406 individuals aged between ≥25 to ≤65 years, both males and females, from Bhil tribal population tracing their origin to Rajasthan (India), were recruited. Blood pressure was measured using digital BP machine; whereas BMI, WHR and WHtR were calculated using the somatometric measurements (height, weight, waist circumference and hip circumference). SPSS vs. 20 was used for the statistical analysis. Male sex, higher age and alcohol consumption was found significantly higher in hypertensive group as compared to that of non-hypertensive group. Underweight was found to pose significantly reduced risk with hypertension. Estimate change analysis revealed that with a unit increase in WHtR there was a significant increase in SBP by +28.95 mm Hg (p = 0.00) and DBP by +16.41 mm Hg (p = 0.04), respectively. In Bhil tribal population WHtR seems to be the best predictor for hypertension.